Identifikasi Jenis Anggang-anggang (Gerris marginatus) di Aliran Sungai Taman Wisata Alam Kerandangan Kabupaten Lombok Barat - Efendi, Rusnadi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Flywheels are a type of insect belonging to the Family Gerridae. Flywheels are insects that are usually found in still waters, such as ponds, rivers and lakes. The aim of this research is to identify the types of flywheels that exist in the river flow of Kerandangan Nature Tourism Park, West Lombok Regency. The type of research used is exploratory descriptive research. Identification of flywheels specimens is based on the identification book from Pennak (1978). The results of the research showed that one type of flywheels was found, namely Gerris sp. in the river flow of the Kerandangan Nature Tourism Park with a total of 529 individuals.